Kebijakan Pemerintah Indonesia Dalam Melindungi Warga Negara Indonesia dan Perdagangan Orang (TPPO) di Malaysia Tahun 2018-2023 - Febriani, Rima; Prayuda, Rendi; Alfajri, Alfajri; Sundari, Rio (UIR Press, 2025)
The purpose of this study is to analyze the implementation of cooperatives and Micro, Small and Medium Enterprises in the Department of Industry, Trade, Cooperatives and Micro, Small and Medium Enterprises in running cooperatives and Micro, Small and Medium Enterprises in Pekanbaru City and to find out the obstacles or obstacles of programs that have been carried out by the Cooperatives and Micro, Small and Medium Enterprises Office, this type of research uses qualitative research methods with observation techniques, interviews and documentation as data collection, The implementation of cooperatives and Micro, Small and Medium Enterprises at the Cooperative Industry and Micro, Small and Medium Enterprises Office, especially in the city of Pekanbaru, is carried out based on the implementation of public policies according to Edward III based on indicators of Communication, Resources, Disposition and Bureaucratic Structure. The results of this study show that the Trade Office of Industrial Cooperatives and Micro, Small and Medium Enterprises has carried out its duties quite well, especially in the field of Micro, Small and Medium Enterprises in the City of Pekanbaru, but many obstacles are experienced such as limited human resources, low awareness of the people of Pekanbaru City in developing Micro, Small and Medium Enterprises, lack of innovation and technological adaptation, and global competition for Micro, Small and Medium Enterprises products